Spectral Anomalies and Spectral Switching With Aperture-Lattice - Singla, Dimple (My University, 2012)
To investigate anomalous spectral behaviour and spectral switching induced by aperture lattice. (2) To investigate the influence of aperture number on spectral switching.
Keywords: Spectral Switching